Handbook on pretrial justice - Scott-Hayward, Christine S., author.
1 online resource.
Keywords: "The Handbook on Pretrial Justice covers the front end of the criminal legal system from pretrial diversion to pretrial detention or release. Often overlooked, the decisions made at the earliest phases of the criminal legal system have huge implications for defendants and their families, the community, and the system itself, and impact the entire criminal legal system. This collection of essays and reports of original research explores the complexities of pretrial decisions and practices and includes chapters in the following broad areas: the consequences of detention, pretrial decision-making, community supervision, and risk assessment. The book also includes a section looking at pretrial justice outside of the U.S. Each chapter summarizes what is known, identifies the gaps in the research, and discusses the theoretical, empirical, and policy implications of the research findings. This is Volume 6 of the American Society of Criminology's Division on Corrections and Sentencing handbook series. The handbooks provide in-depth coverage of seminal and topical issues around sentencing and correction for scholars, students, practitioners, and policymakers"--